Clinical and Electrophysiological Profile of Carpal Tunnel Syndrome in a Tertiary-Level Hospital in Kathmandu, Nepal - Koirala, Sunil Ram; Bastola, Pradeep; Pandey, Poonam; Yadav, Shree Narayan; Gupta, Rajesh Kumar (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy, resulting from compression of the median nerve at the wrist. Symptoms vary with disease severity and typically include numbness, tingling, burning, and pain in the thumb, index, middle, and lateral half of the ring finger. Pain or tingling may radiate to the forearm and shoulder, often accompanied by hand weakness or clumsiness. Limited data exist regarding CTS in the Nepalese population. This hospital-based study aimed to evaluate the clinical and electrophysiological profiles of CTS patients.Method: This retrospective analysis included all patients diagnosed with CTS who underwent nerve conduction studies in the Neurology OPD of the National Academy of Medical Sciences, Bir Hospital, between June 1, 2022, and May 30, 2023. Diagnosis was based on clinical presentation and electrophysiological findings.Results: Ninety-four patients met the inclusion criteria, with a female predominance (76.6%). The mean age was 44.23 ± 10.9 years (range: 23–71). Bilateral CTS was present in 35.1%, while the remainder had unilateral involvement. The mean disease duration was 0.96 ± 0.31 years. Comorbidities included hypothyroidism (24.5%), diabetes mellitus (19.1%), rheumatoid arthritis (3%), and prior trauma or fracture (6.4%). Electrophysiological studies frequently revealed pure sensory median neuropathy and demyelinating changes.Conclusion: CTS predominantly affects middle-aged females in Nepal, with hypothyroidism and diabetes mellitus as common associated conditions. Electrophysiological assessment is crucial for confirming diagnosis and determining severity, with sensory neuropathy and demyelination being the most frequent findings.